2009
DOI: 10.1007/s00330-009-1435-1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional fracture visualisation of multidetector CT of the skull base in trauma patients: comparison of three reconstruction algorithms

Abstract: The purpose of this study was to retrospectively assess the detection rate of skull-base fractures for three different three-dimensional (3D) reconstruction methods of cranial CT examinations in trauma patients. A total of 130 cranial CT examinations of patients with previous head trauma were subjected to 3D reconstruction of the skull base, using solid (SVR) and transparent (TVR) volume-rendering technique and maximum intensity projection (MIP). Three radiologists independently evaluated all reconstructions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 22 publications
1
20
0
3
Order By: Relevance
“…4,[12][13][14] In all children, we found that 2D+3D CT increased the sensitivity (81.3%, p < 0.05) when compared with 2D CT only (74.5%) in the diagnosis of linear skull fractures. In addition, fewer false-negative calls (or undercalls) with 2D+3D (n = 45) when compared with 2D alone (n = 65) showed statistical significance (p < 0.05).…”
Section: Discussionmentioning
confidence: 73%
“…4,[12][13][14] In all children, we found that 2D+3D CT increased the sensitivity (81.3%, p < 0.05) when compared with 2D CT only (74.5%) in the diagnosis of linear skull fractures. In addition, fewer false-negative calls (or undercalls) with 2D+3D (n = 45) when compared with 2D alone (n = 65) showed statistical significance (p < 0.05).…”
Section: Discussionmentioning
confidence: 73%
“…The advantage of three-dimensional reconstruction in emergency patients with skull-base fractures using solid and transparent volume-rendering techniques and maximum intensity projection (MIP) has been examined by Ringl et al [10] . They have ascertained that MIP with regard to sensitivity (P = 0.9) visualizes fractures slightly better than high resolution multiplanar reformation (HR-MPR).…”
Section: Bony Structures In the Head And Neckmentioning
confidence: 99%
“…Damage detection at 24-48 h after onset of symptoms is not always possible. Therefore, Totaro et al [45] have concluded that diffusion-weighted imaging in the postacute phase of cerebral ischemia in patients in whom CT did not yield a definite diagnosis could be the solution [10] . MRA, with its improvements in parallel imaging at high-field strength, with resultant high-spatial-resolution data acquisition over large fields of view has become an interesting alternative to the traditional catheter-directed selective angiography [46] .…”
Section: Blood Vesselsmentioning
confidence: 99%
“…Despite these documented 3D applications of conventional MDCT and CBCT, there has been no systematic assessment of the specific CT image acquisition parameters 8 as well as the 3D reconstruction techniques 9 that will provide the most accurate linear, angular, volumetric, and surface area measurements. Assessments of 3D-CT renderings (MDCT or CBCT) using human body parts, bony remains, phantom objects, and anatomical models have consistently found linear measurements to be statistically accurate, irrespective of CT acquisition parameters 1020 .…”
Section: Introductionmentioning
confidence: 99%